Enhancing management integrity through auditability concept: a literature review. Issue 4 (14th November 2016) - Johari, Razana Juhaida; Sayed Hussin, Sayed Alwee Hussnie
Abstract : Purpose: The purpose of this paper is to highlight the importance of auditability concept as one of the corporate governance indicators that could increase the management integrity practices and public confidence toward the organizations. Nowadays, most business organizations having issues related to the complexity of the transactions, which make it difficult to collect audit evidence and eventually may affect the company's good governance. This paper highlights the importance of management integrity practices through auditability concept that needs to be emphasized in today's business environment. Auditability is the ability of the organizations to provide accurate adequate records to be audited by auditors. Design/methodology/approach: A number of databases in fields such as social sciences and economics were used to acquire literature on the topic. Findings: A discussion on the auditability concept through auditability triangle and auditability model and how management could strengthen the governance practices. Originality/value: This paper provides new inputs to related parties in preparing more comprehensive guidelines on the implementation of auditability practice among the management as to increase the public confidence on the reported financial statements.